2018
DOI: 10.3390/lubricants6040108
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication Regime Classification of Hydrodynamic Journal Bearings by Machine Learning Using Torque Data

Abstract: Hydrodynamic journal bearings are used within a wide range of machines, such as combustion engines, gas turbines, or wind turbines. For a safe operation, awareness of the lubrication regime, in which the bearing is currently operating, is of great importance. In the current study, highspeed data signals of a torque sensor, sampled with a frequency of 1000 hz in a time range of 2.5 s, obtained on a journal bearing test-rig under various operating conditions, are used to train machine learning models, such as ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The ANN predictions show high agreement to the experimental data and the authors stated that such ANNs can effectively reduce the number of future experiments. Furthermore, Moder et al [77] showed that supervised ML algorithms can be used to predict the lubrication regime of hydrodynamic radial journal bearings based on given torques. Therefore, the torque time series were first analyzed using Fast Fourier Transformation (FFT) and manually assigned to lubrication regimes.…”
Section: Sliding Bearingsmentioning
confidence: 99%
“…The ANN predictions show high agreement to the experimental data and the authors stated that such ANNs can effectively reduce the number of future experiments. Furthermore, Moder et al [77] showed that supervised ML algorithms can be used to predict the lubrication regime of hydrodynamic radial journal bearings based on given torques. Therefore, the torque time series were first analyzed using Fast Fourier Transformation (FFT) and manually assigned to lubrication regimes.…”
Section: Sliding Bearingsmentioning
confidence: 99%
“…In addition, AI/ML algorithms can be used to predict lubricant film formation and friction behavior in thermo-hydrodynamically (THL) and thermo-elastohydrodynamically lubricated (TEHL) contacts. For example, Moder et al [27] used highspeed data signals of a torque sensor obtained from a journal bearing test-rig to train ML models for predicting lubrication regimes (Figure 5). Main results showed that deep and shallow neural networks performed equally well, reaching high accuracies.…”
Section: Lubrication and Fluid Film Formationmentioning
confidence: 99%
“…Wear and misalignment identification on journal bearings using ANNs was presented by Saridakis et al [17]. The characterization of the lubrication regimes of journal bearings by machine learning (ML) presented by Moder et al [18]. Otero et al [19] presented the ability of ANNs to predict the friction coefficient, learn by experimental data.…”
Section: Introductionmentioning
confidence: 99%